New country records of broad-nosed weevils (Coleoptera, Curculionidae, Entiminae) from Colombia - María Fernanda Bermúdez-Higinio; Gabriela Argote-Pabón; Jean Gamboa; María Guadalupe del Río; Jennifer C. Girón-Duque (Check List, 2025)
New taxonomic records of broad-nosed weevils from Colombia are presented for the genus Phaops Sahlberg, 1823 and 11 species: Compsus argyreus (Linnaeus, 1758); Compsus fossicollis Kirsch, 1889; Cydianerus ornatus (Pascoe, 1881); Naupactus annae Bordón, 1997; Oxyderces cinereus (Hustache, 1938); Phaops thunbergii (Dalman, 1823); Platyomus atrosignatus Lucas, 1857; Platyomus latacungae Kirsch, 1889; Platyomus septempunctatus Boheman, 1833; Plectrophoroides lutra (Schoenherr, 1826); and Promecops aemulus Voss, 1934. Specimens were collected mainly from the Colombian Amazon. Material examined, specimen photographs, and distribution maps are provided for each species.